The influence of kinesthetics, attitude and motivation on the learning results of sports education - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, M. Sahib (Universitas Nusantara PGRI Kediri, 2019)
The study aims at identifying the influence of kinesthetics, attitude and motivation on the learning results of Sports Education. The nature of the study is path analysis. Within the study, the exogenous variables are kinesthetics (X1), attitude (X2) and motivation (X3) while the endogenous variable is the learning results of Sports Education. Then, the samples that have been selected for the conduct of the study are 40 male students from Grade XI of Bantaeng Vocational High School. The data that have been gathered are analysed by means of inferential statistical analysis namely the regression test. The results of the study show that Kinesthetics, Attitude and Motivation have influence on Learning Results of Sports Education. Furthermore, the results of the study also show that Kinesthetics and Attitude by means of Motivation also have influence on Learning Results of Sports Education. However, within the conduct of the study the researcher only involves a few samples. Therefore, the results of the study might be developed further in the future studies with more methods and samples.